Neuroprotective role of GABAB receptor modulation against streptozotocin-induced behavioral and biochemical abnormalities in rats. (15th August 2017) - Kumar, Kushal; Kaur, Harmanpreet; Deshmukh, Rahul
Highlights: ICV-STZ produces cognitive deficit and biochemical abnormalities in rats. GABAB receptor modulation affects cognitive functions in rats. CGP3548 attenuates experimental dementia in rats. Abstract: Stimulation as well as inhibition of GABAB (Gamma amino butyric acid) receptors has been reported to show beneficial effects in Alzheimer's disease (AD). Experimental evidences suggest that the use of GABAergic agents could influence learning and memory. The present study was designed to investigate the possible role of GABAB receptors in streptozotocin (STZ)-induced behavioral and biochemical abnormalities in rats. Herein STZ was infused (3 mg/kg) bilaterally on alternate days (day 1 and day 3) to produce experimental dementia in rats. STZ-infused rats were then treated with baclofen (GABAB R agonist) 5 and 10 mg/kg i.p. and CGP35348 (GABAB R antagonist) 25 and 50 mg/kg i.p. one week following STZ infusion for 15 days. Cognitive functions were assessed by using Morris water maze (MWM) and object recognition task (ORT). Levels of malondialdehyde (MDA.), reduced glutathione (GSH), andacetylcholinesterase (AChE) were determined to evaluate oxidative stress and cholinergic function. STZ-infused rats showed decreased memory retention, elevated levels of MDA, increased AChE activity, reduced GSH levels. The combination of STZ with increasing doses of Baclofen further induced a higher decrease in memory retention and increase in oxidative stress. CGP35348 restored cognitive functions and AChE activity in STZ-infused rats. The cognitive enhancement following CGP35348 may be due to its ability to restore cholinergic, serotonergic and dopaminergic function, and its antioxidant activity. Therefore, it would be safe to conclude that the pharmacological blockade of GABAB receptors would be therapeutic in the management of cognitive disorders such as Alzheimer's disease.